Penerapan Regresi Logistik Biner Pada Faktor-Faktor Perceraian di Kota Medan - Fitriani Fitriani; Hendra Cipta; Rina Widyasari (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
Divorce is a court decision on the termination of a marriage. Divorce brings with it a negative impact, especially on the children of the couple's marriage. Children who are victims of divorce tend to be prone to feeling afraid, sad, guilty to trigger stress and depression in children which then has a bad impact on relationships during the child's growth and development. Therefore, it is necessary to conduct an analysis to find out the factors of divorce. In this research, the analysis used is binary logistic regression with the response variables in the binary category of divorce, namely “cerai talak” and “cerai gugat”. While the stimulus variables in this study were 13 objects obtained based on secondary data documentation of Courts. The results of this research are obtained five factors that have a significant effect, namely age at marriage and profession of who filing for divorce and divorce defendant, as well as the education of who filing for divorce. The interpretation of the results of binary logistic regression analysis shows that, the age of divorced defendant at the time of marriage has a 1,15 times greater effect on the cerai gugat, while the age of who filed for divorce has a 0.68 times greater effect on the cerai talak. Keywords: Divorce, Factors, Binary Logistics Regression